AltitudeOmics: Baroreflex Sensitivity During Acclimatization to 5,260 m - Bourdillon, Nicolas; Yazdani, Sasan; Subudhi, Andrew W.; Lovering, Andrew T.; Roach, Robert C.; Vesin, Jean-Marc; Kayser, Bengt (Frontiers in Physiology, 2018)
Introduction: Baroreflex sensitivity (BRS) is essential to ensure rapid adjustment to variations in blood pressure (BP). Little is known concerning the adaptive responses of BRS during acclimatization to high altitude at rest and during exercise. Methods: Twenty-one healthy sea-level residents were tested near sea level (SL, 130 m), the 1st (ALT1) and 16th day (ALT16) at 5,260 m using radial artery catheterization. BRS was calculated using the sequence method (direct interpretation of causal link between BP and heartrate). At rest, subjects breathed a hyperoxic mixture (250 mmHg O2, end tidal) to isolate the preponderance of CO2 chemoreceptors. End-tidal CO2 varied from 20 to 50 mmHg to assess peripheral chemoreflex. Rebreathing provoked incremental increase in CO2, increasing BP to assess baroreflex. During incremental cycling exercise to exhaustion, subjects breathed room air. Results: Resting BRS decreased in ALT1 which was exacerbated in ALT16. This decrease in ALT1 was reversible upon additional inspired CO2, but not in ALT16. BRS decrease during exercise was greater and occurred at lower workloads in ALT1 compared to SL. At ALT16, this decrease returned toward SL values. Discussion/Conclusion: This study is the first to report attenuated BRS in acute hypoxia, exacerbated in chronic hypoxia. In ALT1, hypocapnia triggered BRS reduction whilst in ALT16 resetting of chemoreceptor triggered BRS reduction. The exercise BRS resetting was impaired in ALT1 but normalized in ALT16. These BRS decreases indicate decreased control of BP and may explain deteriorations of cardiovascular status during exposure to high altitude.